Blood & Thunder. Volume 1, The prisoner on Cell Block X - Cereno, Benito (Image Comics, Inc., 2025)
"Bounty hunter Akeldama 'Blood' Bledsoe and her cantankerous talking gun Thunder are the best out there at bringing in the bad guys. However, when the galaxy's most dangerous criminal breaks out of prison, Blood's hunt delivers her down a path that will unlock secrets about her past, present, and future... and that's when things get really bad"--Page 4 of cover.